The Role of Key Stakeholders in the International Joint Venture Negotiations: Case Studies from Eastern Europe - Brouthers, Keith D.; Bamossy, Gary J. (Journal of International Business Studies, 1997)
Recent literature has suggested that a key stakeholder may be able to shift the balance of bargaining power during a joint venture negotiation, and thus change the outcome of the process. This paper explores the role of central and eastern European transitional governments as key stakeholders, and how they influence international joint venture negotiations. This role is described and analyzed by examining eight dyads of western European and central/eastern European enterprises that have recently negotiated agreements. The findings suggest that transitional governments as key stakeholders intervene at different stages of the negotiation process, have both direct and indirect influences on the process, and that they can change the balance of power in the negotiations, sometimes to the detriment of their own state-owned enterprise.